Scaling Measurements of the Effect of Surface Slant on Perceived Lightness. (February 2014) - Madigan, Sean C.; Brainard, David H.
The light reflected from an object depends on its reflectance, the illumination, and the pose of the object within the scene. An observer is called lightness constant if the perceived reflectance (lightness) of achromatic objects stays the same despite variation in object-extrinsic factors such as illumination and pose. Here, we used a dissimilarity scaling task to measure lightness constancy as the intensity of the illuminant and the slant of test surfaces were varied. Across two experiments, we had observers rate the dissimilarity of flat grayscale test stimulus pairs. The test stimuli were real illuminated surfaces, not computer simulations. Each test stimulus was seen in its own illuminated chamber, with the two chambers viewed side by side. We varied test surface reflectance, chamber illumination intensity, and the slant of the test in relation to the single light source in each chamber. Data were analyzed using nonmetric multidimensional scaling. The data were well-described by a one-dimensional perceptual representation. This representation was consistent across observers, revealed partial lightness constancy with respect to a change in illumination intensity, and no lightness constancy with respect to changes in surface slant. An additional experiment using a matching procedure and the same stimulus set, however, revealed moderate constancy with respect to changes in surface slant. The difference in results between the two methods is interesting, but not understood.